A History of Christianity : an introductory survey - Early, Joseph, Jr. (Nashville, Tennessee : B & H. Academic, 2015)
A History of Christianity examines the development of Christianity from its biblical foundations to modern times. While seeking to be comprehensive, historian Joseph Early Jr. centers on key events, people, theological developments, and conflicts that have shaped Christianity over its two-thousand-year history. He also presents the development of Christianity within the social, political, and economic challenges of the times. In doing so, he paints a clear, detailed, and balanced picture of the opportunities and struggles faced by the church and the contributions made by significant people, institutions, and traditions. A History of Christianity is an ideal introductory survey for undergraduate students and any reader who desires to know more about the broad scope of Christianity.
The New Christian World-- Globalization in the twentieth and twenty-first centuries
Includes bibliographical references and index.
Keywords: Church history